2016
DOI: 10.2217/nnm-2016-0150
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Commitment of Human Circulating Multipotent Cells By Carbon nanotube-polymer Scaffolds and Biomimetic Peptides

Abstract: This work suggests the scaffold-peptides system combined with autologous hCMCs as a functional biomimetic, self-standing prototype for neural regenerative medicine applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…A), suggesting a possible correlation among in vivo regeneration following the implantation of CLP‐MB and the in vitro development of cells with anti‐inflammatory functionality, proliferative activity and high grade of stemness. In particular, CPL‐CMC subcultures from 4th to 20th generation demonstrated a doubling population time of 21 ± 1.85 hrs, which was significantly shorter than that of other multipotent cells isolated from human peripheral blood (Fig. B).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A), suggesting a possible correlation among in vivo regeneration following the implantation of CLP‐MB and the in vitro development of cells with anti‐inflammatory functionality, proliferative activity and high grade of stemness. In particular, CPL‐CMC subcultures from 4th to 20th generation demonstrated a doubling population time of 21 ± 1.85 hrs, which was significantly shorter than that of other multipotent cells isolated from human peripheral blood (Fig. B).…”
Section: Resultsmentioning
confidence: 89%
“…Opening new perspectives in autologous stem cell research, L-PRF products prepared according to Caloprisco's method [10] have been found to deliver stem cell-like cells with unique phenotypic features, functionality and differentiative potentialities in comparison with endothelial/haematopoietic progenitors [29,30], mesenchymal stem cells (MSCs) [27,31,32], embryonic-like stem cells [11,[33][34][35][36] and circulating multipotent cells [12,13,25,37]. Isolated by minimal in vitro manipulation of CPL membranes, CMC cells showed fibroblast-like morphology, long-lasting proliferative activity and high expression of CD44/HCELL, CD49f and CXCR4.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) and fat-derived stem cells are widely used for regenerative-medicine purposes [5][6][7]. Among blood-derived stem cells, human circulating multipotent stem cells (hCMCs) [8] represent an interesting model as they can differentiate into progenitors for several mesenchymal tissue types, such as adipocytes, osteoblasts, chondroblasts, or muscle cells in response to different culture conditions. These cells are extremely sensitive to changes in the microenvironment, and respond to biomimetic stimuli by sudden variations in gene expression; importantly, when specific growth factors are added, they can also commit to neuronal differentiation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Conductive CNTs represent an established nanofiller for boosting neuronal commitment and differentiation [15][16][17][18][19][20]. FDA-approved poly(L-lactic) acid (PLLA) is widely used in regenerative medicine, and scaffolds consisting of CNTs dispersed in a PLLA matrix (CNT@PLLA) were able to commit hCMCs toward a neuronal lineage even in the absence of exogenous neurotrophins, highlighting their biomimetic potential [8].…”
Section: Introductionmentioning
confidence: 99%
“…37,38 While processing the peripheral blood of Vietnamese pigs (VPs) sedated before heart valve surgery, we recently isolated a population of multipotent adherent cells that fulfill some MSC criteria, as defined by the International Society for Cellular Therapy. 29 Due to similarities with human circulating cells previously described, 38 we have named these cells "porcine circulating multipotent cells" (pCMC) and experimentally used to explore the repopulation potential of porcine heart valves decellularized with TriCol procedure (Figure 1). Under no-flow culture condition, pCMC have been showed to be differentially stimulated by AVL and PVL and expressed gene markers correlatable to VIC-and VEC-like phenotypes.…”
Section: Introductionmentioning
confidence: 99%